Oil Consumption in Transport and Economic Growth Nexus: Empirical Evidence from Cameroon - Njoya, Youssouf Nvuh; Njikam, Mouhamed Mbouandi (European Scientific Journal, ESJ, 2018)
This paper focuses on casting light on the causal relationship between oil consumption in transport and economic growth in Cameroon. This paper uses an annual data covering the period 1975-2014, which is a five-step modern time series techniques. They include the Unit root tests, co-integration analysis, and Granger-causality based on error correction model. As a robustness test, we made use of the impulse response function and variance decomposition to portray the correlations between variables. The main result highlighted in the present paper point out the presence of a long-run equilibrium relationship between oil consumption in transport and economic growth. The error correction model shows that an estimated 1% increase in economic growth causes a rise in oil consumption in transport by 1.29 % in the long run. Another results show that there exists bidirectional causality in the long-run relationship and there was no causality in the short-run relationship at the 5% level of significance. The decomposition of the variance and impulse response function indicates a dissymmetric of the variance of the prediction error and the dynamic properties of the system. This study provides a basis for the discussion of energy consumption in transport policies in order to maintain a sustainable economic growth in Cameroon.